2017
DOI: 10.7567/jjap.56.04cc07
|View full text |Cite
|
Sign up to set email alerts
|

Width dependence of platinum and titanium thermistor characteristics for application in room-temperature antenna-coupled terahertz microbolometer

Abstract: For application in a room-temperature microbolometer to detect terahertz waves, “narrow-width effects” on the temperature coefficient of resistance (TCR) and resistivity (ρ) for platinum (Pt) and titanium (Ti) nanowires are investigated. The TCR and ρ of a thermistor could be described by empirical formulas with average measured widths for higher precision. The effect of width on TCR in Pt is lower than that in Ti. The noise equivalent power of the microbolometer could be improved by a factor of 2.3 by replaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…It is worth recalling that the gap between the antenna’s arm is limited to 11.5 μm. Our group had established that a narrower thermistor reduces TCR but increases resistivity [ 52 ]. For the present design, we focus on one thermistor design width of 0.1 μm.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth recalling that the gap between the antenna’s arm is limited to 11.5 μm. Our group had established that a narrower thermistor reduces TCR but increases resistivity [ 52 ]. For the present design, we focus on one thermistor design width of 0.1 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Hence in this report we qualitatively predict the optimum proximity between FDA arms is 2 μm to obtain highest resistance with any number of arms. While in the narrow width case, the decaying resistance can be explained by the size effect caused from the mean free path of conduction electrons, which limits the electrical properties of a metal [20]. From the input impedance simulation results, it is concluded that a proper design process is critical when applying FDA to select desired resonant resistance for the impedance matching with the bolometer.…”
Section: A Radiating Modementioning
confidence: 99%
“…Bolometers without an antenna of the present work were fabricated by the standard Si CMOS technology instead of the complex non-standard lift-off process used in our previously reported works [44,45]. The key advantages of the Si CMOS technology are good reproducibility and universalities of the results.…”
Section: Structure Of Antenna-coupled Bolometersmentioning
confidence: 99%